Chromosome-level de novo genome assembly of wild, anoxia-tolerant crucian carp, Carassius carassius - Laura Marian Valencia-Pesqueira; Siv Nam Khang Hoff; Ole K. Tørresen; Sissel Jentoft; Sjannie Lefevre (Scientific Data)
Abstract Crucian carp (Carassius carassius), a member of the carp family (Cyprinidae), is known for its remarkable anoxia tolerance. The physiological responses and adaptations to anoxia are well documented, but there is a need for better understanding of the molecular regulation and evolutionary mechanisms behind these adaptations. Here we present a high-quality, functionally annotated, chromosome-level genome assembly that can facilitate such further studies. Genomic DNA was obtained from a wild-caught crucian carp specimen and used for PacBio long-read, Illumina short-read and Hi-C sequencing. Short-read mRNA data were used for structural annotation using the BRAKER3 pipeline, while PacBio long-read RNA sequencing data were used for annotation of untranslated regions and refinement of gene-isoform relationships, using the PASA pipeline. The full assembly had a contig-level N50 of 15Mbp in 290 scaffolds and 98.6% of the total length (1.65Gbp) placed in 50 chromosomes. Structural annotation resulted in 82,557 protein-coding transcripts (in 45,667 genes), with a BUSCO completeness of 99.6% and of which 77,370 matched a protein in the UniProtKB/Swiss-Prot database.